2017
DOI: 10.1590/1678-69712016/administracao.v18n2p154-183
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Analysis Between Disclosure on the Internet, Risk and Return in Latin American Companies

Abstract: Purpose: This study sought to examine the extent to which the internet it is utilized as a tool for the disclosure of corporate information, facilitating the transparency of companies in relation to their stakeholders. Originality/gap/relevance/implications: This study differs from previous as it fills a gap in the literature to relate a disclosure measure on the internet with the risk and return of companies in Latin America, since this literature is only possible to identify studies that analyze these varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
(89 reference statements)
2
1
0
Order By: Relevance
“…These two results give an indicator about the importance of financial information for users. These results are also consistent with the findings of prior studies that investigated the actual web-based disclosure practices (e.g., Marston, 2003;Lodhia et al, 2004;Fuertes-Callén et al, 2014;Çalışkan & Güler, 2014;Khan, 2016;Ferreira & Martins, 2017). The users are also interested in the board of director information, which ranked fourth with a mean of 4.3551.…”
Section: Business and Management Horizonssupporting
confidence: 90%
See 2 more Smart Citations
“…These two results give an indicator about the importance of financial information for users. These results are also consistent with the findings of prior studies that investigated the actual web-based disclosure practices (e.g., Marston, 2003;Lodhia et al, 2004;Fuertes-Callén et al, 2014;Çalışkan & Güler, 2014;Khan, 2016;Ferreira & Martins, 2017). The users are also interested in the board of director information, which ranked fourth with a mean of 4.3551.…”
Section: Business and Management Horizonssupporting
confidence: 90%
“…Thus, other studies that found the web-based disclosure for financial information is dominants may support our result (e.g., Çalışkan & Güler, 2014;Khan, 2016;Ferreira & Martins, 2017).…”
Section: Adusers = β 0 + β 1 Husu + β 2 Goqs + β 3 Dilc + β 4 Sorp + supporting
confidence: 87%
See 1 more Smart Citation